IFC Annual Report 2007 : Creating Opportunity - International Finance Corporation (Washington, DC: World Bank, 2012)
This fiscal year the Board of Directors maintained close oversight of International Finance Corporation's (IFC's) efforts to increase and measure its development impact. Directors reaffirmed their support for IFC's strategic directions, including more specific emphasis on agribusiness and small and medium enterprises, as well as IFC's growth strategy. The Board approved a number of investments and joint World Bank-IFC-Multilateral Investment Guarantee Agency (MIGA) country assistance strategies and continued to encourage stronger collaboration, both across the World Bank Group and with partners and stakeholders. Specific issues that Directors discussed with management included IFC's strategy for Africa, the joint Bank Group strategy for the financial sector, the launch of a new IFC-World Bank department focusing on sub-national finance, and several proposals for new products and services with potential to expand IFC's reach in client countries. The Board continued to monitor new methods for measuring outcomes of IFC's investments and advisory services, as well as progress in implementing IFC's environmental and social performance standards. The Board welcomed IFC's strong performance in FY07. These include record levels of financing and expansion of advisory activity in Africa and the Middle East, as well as measurable progress in a number of frontier markets and strategic sectors.